2009
DOI: 10.1007/s10826-009-9291-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Psychosocial Factors with Maternal Confidence Among Japanese and Vietnamese Mothers

Abstract: We conducted this cross-sectional study among 392 Japanese and 294 Vietnamese mothers who attended routine child health visits in a Japanese city and at a tertiary hospital in Vietnam, in order to investigate the prevalence and associated sociodemographic, parenting, and psychological characteristics of low maternal confidence in child rearing among them. All data were collected from medical files in Japan, and from medical files and self-administered questionnaires in Vietnam. The proportion of mothers withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…In many of the research papers, the authors did not discuss the degree of attrition or the impact that such 'self-selection' bias may have had on the results. Eleven studies mentioned this issue as a consideration or limitation (Doherty et al, 2006;Duncan and Bardacke, 2010;Fabian et al, 2005;Fagan, 2008;Goto et al, 2010;Hartung and Hahlweg, 2010;Heinrichs and Jensen-Doss, 2010;Hiscock et al, 2008;Niccols, 2008;Patrick et al, 2008;Svensson et al, 2009). The combination of participant attrition and reach issues indicate that many programmes may be failing to engage parents and meet the goals of universality.…”
Section: Participant/parent Engagement Attrition and Reachmentioning
confidence: 99%
“…In many of the research papers, the authors did not discuss the degree of attrition or the impact that such 'self-selection' bias may have had on the results. Eleven studies mentioned this issue as a consideration or limitation (Doherty et al, 2006;Duncan and Bardacke, 2010;Fabian et al, 2005;Fagan, 2008;Goto et al, 2010;Hartung and Hahlweg, 2010;Heinrichs and Jensen-Doss, 2010;Hiscock et al, 2008;Niccols, 2008;Patrick et al, 2008;Svensson et al, 2009). The combination of participant attrition and reach issues indicate that many programmes may be failing to engage parents and meet the goals of universality.…”
Section: Participant/parent Engagement Attrition and Reachmentioning
confidence: 99%
“…Maternal confidence means a mother’s perception of her ability to care for and understand her children, which is closely related to motherhood adjustment and caring behaviours for infants (Badr 2005, Goto et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The same parenting scoring was explained and used in our accompanying article (Suzuki et al ., ). In brief, the research team discussed its applicability in Vietnam, translated and back‐translated the questions, and confirmed the content accuracy in previous studies (Goto et al ., , ). As shown in Figure , these two scores showed a significant positive correlation (rs = 0.4, P = 0.003).…”
Section: Onsite Activities and Local Responsesmentioning
confidence: 91%
“…Recent studies in Vietnam reported a high prevalence of maternal mental disorders and its association with child health (Fisher et al ., ; Harpham et al ., ). In relation, our previous surveys in Ho Chi Minh City showed that over half of Vietnamese mothers of children aged 1–4 months admitted not having confidence in childrearing, which was associated with depression and lower general self‐efficacy (Goto et al ., ). Taken together, these findings indicate a strong need for maternal mental health support to be incorporated into the maternal and child health program in Vietnam.…”
Section: Introductionmentioning
confidence: 97%